2014
DOI: 10.1016/j.molonc.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of platinum response in human high‐grade serous ovarian cancer patient‐derived xenografts

Abstract: Introduction Improvement in the ability to target underlying drivers and vulnerabilities of high-grade serous ovarian cancer (HG-SOC) requires the development of molecularly annotated pre-clinical models reflective of clinical responses. Methods We generated patient-derived xenografts (PDXs) from consecutive, chemotherapy-naïve, human HG-SOC by transplanting fresh human HG-SOC fragments into subcutaneous and intra-ovarian bursal sites of NOD/SCID IL2Rγnull recipient mice, completed molecular annotation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
174
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(186 citation statements)
references
References 33 publications
11
174
1
Order By: Relevance
“…19), including breast (30,31), colorectal (32,33), lung (34), pancreatic cancers (35,36), and glioblastoma (37,38). While we were preparing this manuscript, two papers were published on tumor grafts obtained from ovarian tumors, one focusing on a small series of high-grade serous type (13), whereas the other presenting a large tumor bank of ovarian cancer of different histotype (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19), including breast (30,31), colorectal (32,33), lung (34), pancreatic cancers (35,36), and glioblastoma (37,38). While we were preparing this manuscript, two papers were published on tumor grafts obtained from ovarian tumors, one focusing on a small series of high-grade serous type (13), whereas the other presenting a large tumor bank of ovarian cancer of different histotype (14).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell lines are reproducible, easy to use, and useful for studying specific mechanisms, but their resemblance to the original tumor and thus their therapeutic predictive value is very limited (12). Two studies describing ovarian cancer patientderived xenografts have been recently published (13,14). However, in those studies little characterization was carried out in relation to the recently proposed origin and pathogenesis of ovarian cancer (i.e., type I or type II), that is now basis for novel target therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of PDXs, in which small pieces of undigested primary tumors are serially passaged in immunocompromised mice, has ushered in a new era of precision medicine, where mice function as avatars to evaluate patient-specific therapies (22)(23)(24)(25)(26). Some of the limitations of PDXas are the serial passaging of the tumors, which can be lengthy and cause loss of clonal diversity, and replacement of human stroma and human vasculature (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…50 In the case of ovarian cancer, tumors with Mcl-1 amplification have been found to be particularly resistant to conventional platinum-based chemotherapy. 51 The BH3-only protein Noxa is a potent and relatively selective neutralizer of Mcl-1. 34,52 Although the present study demonstrates that MLN4924 induces Noxa upregulation and Mcl-1 neutralization in AML, further studies are required to determine whether a similar mechanism will be observed in other hematological malignancies or solid tumors.…”
mentioning
confidence: 99%